Auditoria interna como sistema de control en las actividades económicas y administrativas de la cámara de comercio de Quevedo año 2010 - Castillo Rengel, Cecilia Marisol (2012)
The research entitled "Internal Audit and control system in the areas of Economics and Administrative Chamber of Commerce Quevedo Year 2010", allowed the development and compilation of the results obtained by the Internal Audit conducted based controls systems economic areas - Management within the institution. This research project relates how the implementation of a permanent Internal Audit Systems improve administrative and financial controls of the Chamber of Commerce of Quevedo. The analysis and evaluation of internal control allowed me to identify weaknesses in the Chamber of Commerce Quevedo also know if designated organizational functions are met effectively. Based on the audit results presented some alternative solutions to the problems that have been identified to improve the implementation of existing policies in the institution, in order to decrease the levels of different objectives and scope of the institution, this proposal was presented to the directors of Chamber of Commerce of Quevedo, for subsequent implementation and monitoring.